3D Printing of Bacteria: The Next Frontier in Biofabrication. Issue 4 (April 2018) - Kyle, Stuart
Abstract : Bacterial species are now being mixed with various bioinks to produce functional complex materials using 3D printing. These systems show enormous potential in applications such as bioremediation, sensors that can detect toxic chemicals, oil spill filters, and wound dressings. In particular, 3D-printed minibiofactories represent a potential paradigm shift in biotechnology.